2019
DOI: 10.5853/jos.2019.00332
|View full text |Cite
|
Sign up to set email alerts
|

History of Migraine and Volume of Brain Infarcts: The Italian Project on Stroke at Young Age (IPSYS)

Abstract: Background and Purpose Migraine has been shown to increase cerebral excitability, promote rapid infarct expansion into tissue with perfusion deficits, and result in larger infarcts in animal models of focal cerebral ischemia. Whether these effects occur in humans has never been properly investigated. Methods In a series of consecutive patients with acute ischemic stroke, enrolled in the setting of the Italian Project on Stroke at Young Age, we assessed acute as well as chronic infarct volumes by volumetric mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Ischemic stroke (IS) is associated with high morbidity, high mortality, and high disability, which imposes a heavy burden on society and families, and its incidence has gradually increased in recent years 1,2 . When blood supply is blocked, brain tissue energy is depleted, which is the most direct cause of brain damage.…”
Section: Introductionmentioning
confidence: 99%
“…Ischemic stroke (IS) is associated with high morbidity, high mortality, and high disability, which imposes a heavy burden on society and families, and its incidence has gradually increased in recent years 1,2 . When blood supply is blocked, brain tissue energy is depleted, which is the most direct cause of brain damage.…”
Section: Introductionmentioning
confidence: 99%
“…On the one side, the unbalanced release of endothelial substances and microcirculation thrombosis can trigger cortical spreading depression (39); on the other side, frequent migraine attacks seem to interfere with endothelial functioning (26). In any case, the cerebral cortex of patients with MA seems to be particularly vulnerable to ischemic insults, displaying larger infarct volume (40) and a reduced ratio between hypoperfused and infarcted ischemic areas (41). This sensitivity to ischemic insults can result from different factors, among which the most relevant seems to be an impairment of vascular tone regulation secondary to endothelial dysfunction as an inefficient use of energy supplies (42).…”
Section: Discussionmentioning
confidence: 99%
“…2,4,5 Only one study reported a greater volume of cerebral infarct in patients with migraine, but this study only included patients aged <45 years. 18 Other factors associated with a poor prognosis for stroke were older age and higher scores on the NIHSS scale. This has biological plausibility and agrees with the literature.…”
Section: Discussionmentioning
confidence: 99%